ANTIBACTERIAL ACTIVITIES TEST OF RED GINGER (Zingiber officinale var. rubrum) ETHANOL EXTRACT ON STAPHYLOCOCCUS EPIDERMIDIS - Budianto, Andrea; Dinata, Mulya; Isbandiati, Endang (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Antibiotic is a drug often used against infections caused by bacteria; however, irrational use of antibiotics can cause multidrug resistance (MDR). Staphylococcus epidermidis is a bacteria that has developed an MDR characteristic against antibiotics. Staphylococcus epidermidis is a normal opportunistic flora. Said bacteria can produce a biofilm that enables the bacteria to adhere to prosthetic devices and enter the bloodstream. Red ginger (Zingiber officinale var. rubrum) is a medicinal plant considered antibacterial for its secondary metabolites.Purpose: This study aims to determine the antibacterial effect of red ginger (Zingiber officinale var. rubrum) ethanol extract against Streptococcus epidermidis using a non-equivalent control group design study.Method: Red ginger (Zingiber officinale var. rubrum) ethanol extract was made with the maceration method. This study uses a microdilution test on 96 well plates. The absorbance value was read using a spectrophotometer to determine the Minimum Inhibitory Concentration (MIC) value, and streaking agar was used to find the Minimum Bactericidal Concentration (MBC) value.Result: The result shows that the red ginger (Zingiber officinale var. rubrum) ethanol extract at a concentration of 62,5 Î¼g/mL inhibits 75% of bacteria growth, at 125 Î¼g/mL inhibits 60% of bacteria growth, at 250 Î¼g/mL inhibits 45% of bacteria growth, at 500Î¼g/mL inhibits 65% of bacteria growth and at 1.000Î¼g/mL inhibits 50% of bacteria growth. The streaking agar test result shows bacteria growth on every concentration.Conclusion: Red ginger (Zingiber officinale var. rubrum) ethanol extract in the concentration range of 62,5-1.000 Î¼g/mL have no MIC and MBC value against Staphylococcus epidermidis.Â